(untitled) (Bangladesh Journal of Psychiatry, 2017)
Schizophrenia is one of the major mental disorders which affect individuals thinking ability, social interaction or attention. It affects persons entire quality of life. The purpose of the study was to find out the quality of life of schizophrenic patient in Bangladesh. Cross sectional study design was used to conduct this study. The convenient sampling procedure was used throughout the process of participants selection and the numbers of respondents were 83. The study was carried out at National Institute of Mental Health and Hospital (NIMH), Dhaka. Data was collected by using face to face interview with a structured questionnaire WHOQOL-BREF (The World Health Organization Quality of Life- BREF) scale. It was found that most of the participants lead poor to moderate quality of life in four domains of the WHOQOL-BREF scale. Results showed that mean scores were for physical health (mean 2.7, SD+0.106); psychological health (mean 2.108, SD +0.0787); social relationship (mean 2.226; SD+0.116) and environmental health (mean 2.47; SD+0.077).This study indicated that, quality of life poor on psychological domain. It was also found statistically significance with age and social relationship domain (p value 0.005< 0.05); marital status and physical health domain (p value 0.004<0.05); educational level and physical health domain (p value 0.005<0.05) and environmental health domain (p value 0.025<0.05). There were no statistically significant difference between gender and other variables. Schizophrenia affects all aspects of persons life such as physically, psychologically, socially and economically. Schizophrenic patients as well as their family members led very poor quality of life. Bang J Psychiatry June 2015; 29(1): 30-34